One-Year Outcome After Endovascular Treatment for Acute Basilar Artery Occlusion. Issue 1 (January 2022) - Li, Fengli; Sang, Hongfei; Song, Jiaxing; Guo, Zhangbao; Liu, Shuai; Luo, Weidong; Yuan, Junjie; Qiu, Zhongming; Huang, Jiacheng; Chen, Luming; Li, Linyu; Wu, Deping; et al.
Abstract : Background and Purpose: The BASILAR registry, a nationwide prospective nonrandomized study conducted in China, enrolled consecutive patients with acute basilar artery occlusion receiving endovascular treatment or conventional-treatment from January 2014 to May 2019. This article aimed to report the results of clinical follow-up at one year among these patients. Methods: The primary outcome was the modified Rankin Scale at one year, assessed as a common odds ratio using ordinal logistic regression analysis adjusted for prespecified prognostic factors. Secondary outcomes included the modified Rankin Scale-based outcome group at one year (0–1, 0–2, or 0–3) and all-cause death. Results: Of the 829 patients enrolled in the original BASILAR registry, one-year data were available for 785 patients (94.7%). The distribution of outcomes on the modified Rankin Scale favored endovascular treatment over conventional-treatment (adjusted common odds ratio, 4.50 [95% CI, 2.81–7.29]; P <0.001). The cumulative one-year mortality rate was 54.6% in the endovascular treatment group versus 83.5% in the conventional-treatment group (adjusted odds ratio, 4.36 [95% CI, 2.69–7.29]; P <0.001). Conclusions: The beneficial effect of endovascular treatment on functional outcome at one year in patients with acute basilar artery occlusion is similar to that reported at 90 days in the original study. REGISTRATION: URL: http://www.chictr.org.cn ; Unique identifier: ChiCTR1800014759. Abstract : Supplemental Digital Content is available in the text.